Is device-measured physical activity associated with musculoskeletal disorders among young adult Finnish men? - Sipilä, Lumi; Sievänen, Harri; Raitanen, Jani; Kyröläinen, Heikki; Vasankari, Tommi; Vaara, Jani P.; Honkanen, Tuomas (Frontiers in Sports and Active Living, 2024)
Background Musculoskeletal (MSK) disorders represent a significant burden to society and can be unpleasant for the affected individuals. Physical activity (PA) can prevent MSK disorders while conferring other health benefits. The present study aimed to investigate associations between device-measured PA and perceived MSK disorders among young adult men. Methods PA at different intensity levels, standing, and sedentary behavior were measured with a hip-worn accelerometer in a cohort of 422 young adult Finnish men aged 26 years on average. The incidences of three common MSK disorders (viz., knee pain, lumbar radicular pain, and lumbago pain) during the last month were inquired by a questionnaire. Binary logistic regression was used to examine the associations between the MSK outcomes and explanatory PA variables (PA times at different intensity levels, standing, and sedentary times). The models were controlled for age, education, smoking, BMI, and maximal oxygen uptake. Results PA, standing, and sedentary times were not significantly associated with the incidence of perceived MSK pain during the last month, except for lumbago pain. Lumbago pain was slightly more probable if the time spent in light PA increased, even after controlling for potential confounding factors, including moderate-to-vigorous PA, with an odds ratio (OR) of 1.07 (95% CI: 1.02–1.14). Sedentary time showed an opposite association, with an OR of 0.98 (95% CI: 0.96–1.00). Conclusions There were neither positive nor negative clinically meaningful associations between PA and recent MSK disorders among young adult men. The result is surprising and requires further confirmation.